Stress levels as a rationale for the establishment of an employee recreation programme in the Department of Correctional Services in South Africa - Van Wyk, Johannes G.U. (University of Pretoria, 2013)
Dissertation (MA (Human Movement Science))--University of Pretoria, 2006.